Proceedings of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Confer 2021
DOI: 10.18653/v1/2021.acl-long.372
|View full text |Cite
|
Sign up to set email alerts
|

A Span-Based Model for Joint Overlapped and Discontinuous Named Entity Recognition

Abstract: Research on overlapped and discontinuous named entity recognition (NER) has received increasing attention. The majority of previous work focuses on either overlapped or discontinuous entities. In this paper, we propose a novel span-based model that can recognize both overlapped and discontinuous entities jointly. The model includes two major steps. First, entity fragments are recognized by traversing over all possible text spans, thus, overlapped entities can be recognized. Second, we perform relation classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 50 publications
0
37
0
Order By: Relevance
“…Recent years, a body of literature emerged on span-based models, which were compatible with both flat and nested entities, and achieved SOTA performance (Eberts and Ulges, 2020;Yu et al, 2020;Li et al, 2021). These models typically enumerate all possible candidate text spans and then classify each span into entity types.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years, a body of literature emerged on span-based models, which were compatible with both flat and nested entities, and achieved SOTA performance (Eberts and Ulges, 2020;Yu et al, 2020;Li et al, 2021). These models typically enumerate all possible candidate text spans and then classify each span into entity types.…”
Section: Related Workmentioning
confidence: 99%
“…2 In addition, some studies have also reported that incorrect boundary is a major source of entity recognition error Eberts and Ulges, 2020). Recently, span-based models have gained much popularity in NER studies, and achieved state-ofthe-art (SOTA) results (Eberts and Ulges, 2020;Yu et al, 2020;Li et al, 2021). This approach typically enumerates all candidate spans and classifies them into entity types (including a "non-entity" type); the annotated spans are scarce and assigned with full probability to be an entity, whereas all other spans are assigned with zero probability.…”
Section: Introductionmentioning
confidence: 99%
“…Fisher and Vlachos (2019) proposed a neural network that merges NEs or tokens to generate nested structure and labels them. Several recent researches applied multi-layer GCN to accomplish nested NER (Li et al, 2021;Luo and Zhao, 2020). These are practical methods, nonetheless, the existing models with a huge depth are computationally impractical.…”
Section: Related Workmentioning
confidence: 99%
“…Team Abrosimov_Kirll (Saldon) used the span-based Sodner model (Li et al, 2021) that can recognize both overlapped and discontinuous entities jointly. The model is based on the graph convolutional network architecture.…”
Section: Participants' Submissionsmentioning
confidence: 99%